CULTURAL INFLUENCES ON STUDENT SELF-EFFICACY: A LITERATURE REVIEW ACROSS EDUCATIONAL CONTEXTS - Lola Mustafa Loka; Zarina Akbar; Iriani Indri Hapsari (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Self-efficacy is defined as an individual's belief in their ability to achieve a certain level of performance, which can influence various important aspects of their life. This article identifies and analyzes various cultural dimensions that affect the formation and manifestation of students' self-efficacy, as well as explores the variations in the effects of self-efficacy within educational contexts. The analysis was conducted on literature obtained from the Google Scholar database over the past 11 years (2015 - 2025). The final sample consisted of 20 articles that presented diverse findings on how cultural values influence individuals’ beliefs in their own capabilities in educational settings. The literature review results indicate that Hofstede’s cultural dimensions such as individualism versus collectivism, power distance, uncertainty avoidance, long-term versus short-term orientation, and indulgence versus restraint play significant roles in shaping how students assess and develop their self-efficacy. Furthermore, cross-cultural studies show that self-efficacy has varying effects on key educational outcomes, including academic achievement, student’s mental health, career exploration, motivation, and learning approaches. This study highlights the importance of intervention strategies that consider cultural values and practices to optimize the development of self-efficacy, which in turn contributes to both academic success and psychological well-being of students in educational contexts.